Business Location and Success: The Case of Internet Café Business in Indonesia - Indarti, Nurul (Gadjah Mada International Journal of Business, 2004)
This research aims to examine the relationship between business location decision and business success. The case is Internet café business in Indonesia. This research is addressed to answer these main questions: (1) what factors do underlie location decision for an Internet café business?; and (2) does location decision determine success of Internet café business? A field research is conducted to answer these questions.Factor analysis applied to 17 location factors reveals five underlying dimensions of business location decision. They are centrality, business environment, business venue, cost, and labor. Based on responses from 93 Internet cafés in three locations (i.e. Yogyakarta, Surabaya, and Lombok), the author finds that favorable location of business is positively related to business success. More specifically, a regression analysis reveals that availability of utilities, proximity to schools/universities and security affect business success in a positive direction, while proximity to highways, being in commercial center affect in a negative direction. The independent variables explain 23 percent of total variance.